Chemistry and biology of the compounds that modulate cell migration. (1st March 2016) - Tashiro, Etsu; Imoto, Masaya
Abstract: Cell migration is a fundamental step for embryonic development, wound repair, immune responses, and tumor cell invasion and metastasis. Extensive studies have attempted to reveal the molecular mechanisms behind cell migration; however, they remain largely unclear. Bioactive compounds that modulate cell migration show promise as not only extremely powerful tools for studying the mechanisms behind cell migration but also as drug seeds for chemotherapy against tumor metastasis. Therefore, we have screened cell migration inhibitors and analyzed their mechanisms for the inhibition of cell migration. In this mini-review, we introduce our chemical and biological studies of three cell migration inhibitors: moverastin, UTKO1, and BU-4664L.